Harmony within the new digital paradigm: management of human factor and balance between new and legacy practices - Calcagno, Camila; Vadnjal, Jaka (Serbian Journal of Management, 2025)
Digitalization has become a central topic within societies and organizations, described as a new paradigm or as the fourth industrial revolution. This is a change taking place at many layers, impacting people’s needs, behaviour and expectations. The purpose of this research is to show that for a digitalization process to be successful, a holistic approach is required where change management practices together with the human factor are at its core. The research was performed doing a sistematic literature review together with a measurement instrument in the form of a comprehensive survey that was filled by respondents across different countries and industries. Based on this research, it is important to understand that the environment in which organizations operate is fast and ever-changing. There are constantly new ways of doing things, new technologies and frameworks that could be implemented, new strategies to be explored, etc. What is not different is the need for change with its human centricity.